Comparison of linear vibration welded joints in three different directions of wood tauari (Couratari oblongifilia). (November 2014) - Zhang, H.; Pizzi, A.; Zhou, X.; Lu, X.; Janin, G.
Abstract : Without any adhesive and other chemical additives, the mechanically induced welding can make good wood joints satisfying the relevant requirements for application. The bonding performances of the wood Tauari ( Couratari oblongifilia ) welded joints in three different directions were studied here: parallel to the wood grain, perpendicular to the wood grain and end grain to end grain. The results show that the compression shear bonding strength of the perpendicularly welded joints was the best, parallel welded joints took the second place while the strength of the end grain butt joints was so small that it could not resist the sewing machine. The figures of scanning electron microscopy and the density profiles show the different structures and density distributions of the welded joints which indicate the reasons behind the big differences of the compression shear bonding strength.